Traditional Chinese medicine and plant-derived natural products in regulating triglyceride metabolism: Mechanisms and therapeutic potential - Zhou Jin; Xiaolong Wang (Elsevier, 2024)
The incidence of cardiometabolic disease is increasing globally, with a trend toward younger age of onset. Among these, atherosclerotic cardiovascular disease is a leading cause of mortality worldwide. Despite the efficacy of traditional lipid-lowering drugs, such as statins, in reducing low-density lipoprotein cholesterol levels, a significant residual risk of cardiovascular events remains, which is closely related to unmet triglyceride (TG) targets. The clinical application of current TG-lowering Western medicines has certain limitations, necessitating alternative or complementary therapeutic strategies. Traditional Chinese medicine (TCM) and plant-derived natural products, known for their safety owing to their natural origins and diverse biological activities, offer promising avenues for TG regulation with potentially fewer side effects. This review systematically summarises the mechanisms of TG metabolism and subsequently reviews the regulatory effects of TCM and plant-derived natural products on TG metabolism, including the inhibition of TG synthesis (via endogenous and exogenous pathways), promotion of TG catabolism, regulation of fatty acid absorption and transport, enhancement of lipophagy, modulation of the gut microbiota, and other mechanisms. In conclusion, through a comprehensive analysis of recent studies, this review consolidates the multifaceted regulatory roles of TCM and plant-derived natural products in TG metabolism and elucidates their potential as safer, multi-target therapeutic agents in managing hypertriglyceridemia and mitigating cardiovascular risk, thereby providing a basis for new drug development.